Task-related focus-on-forms foreign language vocabulary development: Focus on spoken form and word parts. (February 2021) - Soodmand Afshar, Hassan
Abstract: The study explored the impact of task-related focus-on-forms (FonFs) (i.e., focus on spoken form and word parts) on EFL vocabulary development. A total of 130 English language students were randomly assigned to three different experimental conditions adopting a 'comparison group' design. In Group 1, the teacher taught the forty target words by giving their definitions (in the form of target language explanations) and example sentences wherein they were used; hence, the focus was on meaning and use only. Group 2 did the same as that in Group 1. Besides, they focused on the spoken form (i.e., pronunciation) of the target words modelled by the teacher and followed by the participants' choral and individual repetition. In Group 3, besides what was done in Group 2, the participants also focused on word parts as another feature of word form. Vocabulary development was measured by a forty-item multiple choice vocabulary test. The ANOVA results showed significant differences with Group 3 outperforming Group 2, who, in turn, outperformed Group 1 implying that task-related FonFs activities worked. Also, the results of a focus group interview showed focus on spoken form and word parts were both helpful and that the former increased the participants' self-confidence as well. The findings might suggest that focus on word meaning and use plus task-related FonFs could involve deeper processing and yield higher learning gains in foreign language vocabulary development. Highlights: The impact of task-related focus-on-forms (FonFs) on EFL vocabulary was explored. FonFs (i.e. focus on word spoken form and word parts) was found to be effective. Focus on spoken form was found to enhance learners' self-confidence. Word parts were believed to provide a shortcut for word learning.